Pengaruh Supervisi Kepala Sekolah dengan Teknik Kelompok (Meeting) terhadap Peningkatan Prestasi Kerja Guru di Gugus V Nakula Kecamatan Serengan Surakarta - Ismiyatun, Ismiyatun (Universitas Muhammadiyah Surakarta, 2016)
The purposes of this research were based on the above problem statement, therefore, the purposes of the research which would be reached were: 1) To know whether there is influence of the headmaster supervision on the performance of the elementary school teachers in Gugus V Nakula of Serengan Sub-district, Surakarta; 2) To know how much the influence of the headmaster supervision on the performance of the elementary school teachers in Gugus V Nakula of Serengan Sub-district, Surakarta was. This scientific paper applied the School Action Research (PTS) that was an effort of increasing the work discipline of teachers in the teaching learning process through an individual supervision through a technique approach of class visit consisting of two cycles and each cycle consisted of four stages: (1) planning, (2) implementation of action, (3) observation/evaluatiom, and (4) reflection. This School Action Research was conducted in Elementary Schools all over Gugus V Nakula of Serengan Sub-district, Surakarta Municipality. Gugus V Nakula consisted of 5 elementary schools, 2 public elementary schools and 3 private elementary schools SMP only the national standard in the district of Nusa Penida includes two (2 ) regions and villages Desa Lembongan Jungutbatu, with the amount of students was 315 (three hundres and fifteen) students, consisting of 12 (twelve) classes, with the amount of teachers was 31 (thirty one) teachers, 3 (three) people had qualification of S2 (post graduate degree), 28 (twenty eight) people had qualification of S1 (undergraduate degree), 1 (one) person had Diploma I (D1) degree. Based on the results of data analysis, either in cycle I or cycle II, it could be concluded that 1) there was an influence of the headmaster supervision on the performance of 1-6 grades teachers in the elementary schools all over Gugus V Nakula, Serengan Sub-district, Surakarta. It was proved from the analysis scores in the cycle I which the average percentage was 67.26%Â which increased into 78,12%; 2) The amount of influence of the headmaster supverision on the performance of 1-6 grades teachers in the elementary schools all overÂ Gugus V Nakula, Serengan Sub-district, Surakarta in this research was 10.86%